Digitalization and informatization of society as triggers for the transformation of constitutional values - Saulen, Н.; Zhambayev, Е.С.; Sagadiev, А.Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
Information plays a key role. Technological progress due to the Fourth Industrial Revolution, announced in the book of the same name by Klaus Schwab, President of the World Economic Forum in Davos, will rapidly continue to change society in many, if not all, aspects of its life, and there is no doubt that the history of humanity has never known such a level of technological development. For this reason, the relevance of research on new legal relations arising in the digital and information field is beyond doubt. The purpose of this article is to investigate the current state and impact of digitalization and informatization on the transformation of such constitutional values as the right of everyone to privacy, telephone conversations, etc., as well as the right of everyone to freely receive and disseminate information in any way not prohibited by law. We have achieved three results, the most important of which, as we believe, is the proposal on the need to develop an appropriate legal act and introduce into legal circulation such a concept as «Rules for the use of information» (information diet), which, as we believe, requires further research and discussion, with the involvement of narrow-profile specialists, including medical researchers. Based on the judgments of Klaus Schwab, we concluded that such constitutional values as the right of everyone to privacy, personal secrecy, the secrecy of telephone conversations, etc., may disappear in the near future.